Incidence and Associated Factors for Inappropriate Blood Cross Matching in Cardiovascular Thoracic Surgeries at a Tertiary Care Center: A Retrospective Study Using Binary Logistic Regression - Harnroongroj, Saranya; Saezhang, Worachet; Dangkoet, Rattana (Siriraj Medical Journal, 2026)
Objective: To determine the incidence of inappropriate packed red cell (PRC) crossmatching in Cardiovascular Thoracic (CVT) surgeries at a service-focused tertiary care center, and to identify the associated factors for the inappropriate PRC cross-matching. Materials and Methods: A retrospective cross-sectional study was conducted involving 640 patients who underwent CVT surgery between 2022 and 2025. The data reviewed included the patients’ demographics, operative details, and PRC utilization (specifically, crossmatching and transfusion within 24 hours postoperatively). The crossmatch to transfusion (CT) ratio, transfusion probability (%T), and transfusion index (Ti) were calculated. An individual CT ratio > 2.0 was defined as inappropriate crossmatching. Binary logistic regression was used to identify the associated factors for inappropriate PRC crossmatching, and the Youden index to determine the optimal cutoff values. Results: Inappropriate PRC crossmatching occurred in 426 of the 640 cases (66.6%). The overall CT ratio was 2.36, exceeding the recommended threshold limit of 2.0 and suggesting excessive blood ordering. Closed heart surgeries had the highest CT ratio (13.8), followed by thoracic surgeries (4.21). Significant factors associated with inappropriate crossmatching included elective surgery, a pre-operative hematocrit level > 35.4%, and intraoperative blood loss < 275 mL. Conclusion: Inappropriate PRC crossmatching is common in CVT surgeries, with an incidence of 66.6% in this study cohort. Elective procedures, a higher pre-operative hematocrit level, and lower intraoperative blood loss were found to be key predictors for inappropriate PRC crossmatching. These findings highlight the need for more evidence-based transfusion protocols to minimize excessive crossmatching in CVT surgeries, and optimize the utilization of blood resources.